Transient Stability Improvement of the Power Systems - Zaid H. Al-Tameemi; Hayder H. Enawi; Karrar M. Al-Anbary; Hussam M. Almukhtar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
During the last few decades, electrical power demand enlarged significantly whereas power production and transmission expansions has been brutally restricted as a result of restricted resources as well as ecological constrains. Consequently, many transmission lines have been profoundly loading so the stability of power system became as Limiting factor for transferring electrical power. So, maintaining a secure and stable operation of the electric power networks is deemed an imporatant and challenge issue.transient stability of a power system has been gained a considerable attention from researchers dute to it importance . Therefore,this paper sheds light on A substantial number of the adopted techniques, including an inclease in  inertia constant of generator, shunt capacitor, reduction reactance of the transmission line to acheive this purpose. A 7-Machine CIGRE system has been considered a case study. Matlab package has been employed to implement this study. The simulation results show that the transient stability of the repective system enhanced considerably with these techniques.